2000
DOI: 10.1177/019262330002800202
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Effects of the Novel Glucocorticosteroid RPR 106541 Administered to Beagle Dogs by Inhalation

Abstract: The preclinical safety of RPR 106541, a novel 17-thiosteroid, was

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 38 publications
(51 reference statements)
0
13
0
Order By: Relevance
“…Urine cortisol was assayed by radioimmunoassay c validated for use in canine urine 21,22 and urine creatinine was measured in a routine manner in the same laboratory. UCC ratio was calculated from the 2 results (reference range, [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. Additionally, ACTH stimulation was performed at the dogs' homes before 10:00 AM.…”
Section: Endocrine Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Urine cortisol was assayed by radioimmunoassay c validated for use in canine urine 21,22 and urine creatinine was measured in a routine manner in the same laboratory. UCC ratio was calculated from the 2 results (reference range, [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. Additionally, ACTH stimulation was performed at the dogs' homes before 10:00 AM.…”
Section: Endocrine Assessmentmentioning
confidence: 99%
“…[17][18][19] There is little published information regarding the effects of clinically relevant inhalant GC administration to dogs, 13 and we are aware of only a single prospective study examining the effects of any inhalant GC in this species. 20 The purpose of the study reported here was to compare systemic clinical, endocrine, and immunologic effects of inhaled GC (220 mg fluticasone q12h delivered through a spacer device) with PO-administered GC (1 mg/kg prednisone q24h) and placebo. We hypothesized that in healthy dogs the inhalant GC would result in fewer observable clinical effects and less HPAA and immunologic suppression than the PO-administered GC.…”
mentioning
confidence: 99%
“…The best predictor was a combination of studies in multiple species including the rodent, and for certain classes of drug, such as cytotoxic anticancer agents, the mouse alone was reported to best predict for human side effects (Newell et al, 2004). An excellent example of a drug-induced hepatic change in the beagle dog is the vacuolation induced by excessive glucocorticoid administration also referred to as steroid hepatopathy (Dillon et al, 1983;Rutgers et al, 1995;Miller et al, 2000). Figure 9 shows the effect of chronic administration of prednisone to the beagle dog on the liver weight following both a subacute (14 days) and a chronic dosing regime (52 weeks).…”
Section: Drug-induced Nonneoplastic Hepatic Changesmentioning
confidence: 99%
“…48 Our understanding of the mechanisms involved in glucocorticoid-induced osteoporosis is far from complete. Similar effects also occur in laboratory animals treated with corticosteroids.…”
Section: Osteoporosismentioning
confidence: 99%